Transforming Agribusiness in Nigeria for Inclusive Recovery, Jobs Creation, and Poverty Reduction : Policy Reforms and Investment Priorities - Mghenyi, Elliot (Washington, DC: World Bank, 2022)
Nigeria has for decades placed enormous emphasis on diversifying its economy beyond oil and into sectors such as agribusiness and manufacturing. Lack of progress on the diversification agenda could be blamed on weak implementation and misalignment of public spending, but it also reflects more profound underlying issues. For example, declarations that any particular sector should drive diversification without offering clarity on specific investment priorities and expected outcomes will not persuade budget holders to allocate development resources. The lack of clarity also deprives policy makers and practitioners of the information, inspiration, and conviction to develop and execute sector plans that could operationalize diversification.